2(x-1)=3x+4 alguem pode me ajudar a resolver essa equaçoes
Soluções para a tarefa
Respondido por
13
2(x-1) = 3x + 4
2x - 2 = 3x + 4
2x - 3x = 4 + 2
- x = 6 .(-1)
x = - 6
2x - 2 = 3x + 4
2x - 3x = 4 + 2
- x = 6 .(-1)
x = - 6
lele1114:
ok
Respondido por
8
2(x-1)=3x+4
2x -2 = 3x +4
2x -3x = 4 +2
-x = 6
x = -6
2x -2 = 3x +4
2x -3x = 4 +2
-x = 6
x = -6
Perguntas interessantes
Biologia,
11 meses atrás
Geografia,
11 meses atrás
ENEM,
11 meses atrás
Matemática,
1 ano atrás
Informática,
1 ano atrás
Matemática,
1 ano atrás